2011
DOI: 10.1038/leu.2011.78
|View full text |Cite
|
Sign up to set email alerts
|

Continuing high early death rate in acute promyelocytic leukemia: a population-based report from the Swedish Adult Acute Leukemia Registry

Abstract: 9Swedish Acute Myeloid Leukemia Group, SwedenOur knowledge about acute promyelocytic leukemia (APL) patients is mainly based on data from clinical trials, whereas population-based information is scarce. We studied APL patients diagnosed between 1997 and 2006 in the populationbased Swedish Adult Acute Leukemia Registry. Of a total of 3897 acute leukemia cases, 3205 (82%) had non-APL acute myeloid leukemia (AML) and 105 (2.7%) had APL. The incidence of APL was 0.145 per 100 000 inhabitants per year. The median a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
200
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(236 citation statements)
references
References 23 publications
17
200
3
5
Order By: Relevance
“…Consolidation treatment consisted of one to three courses of combination therapy including intermediate-or high-dose Ara-C. Treatment of APL followed the national guidelines with ATRA in combination with either idarubicin or daunorubicin [13]. Palliative treatment included supportive treatment with transfusions with or without low-dose cytarabine, hydroxyurea, and/or thioguanin.…”
Section: Methodsmentioning
confidence: 99%
“…Consolidation treatment consisted of one to three courses of combination therapy including intermediate-or high-dose Ara-C. Treatment of APL followed the national guidelines with ATRA in combination with either idarubicin or daunorubicin [13]. Palliative treatment included supportive treatment with transfusions with or without low-dose cytarabine, hydroxyurea, and/or thioguanin.…”
Section: Methodsmentioning
confidence: 99%
“…33,95,96 Park et al 97 reported 1400 cases of APL from 1992 to 2007, the overall ED rate was 17.3%, and only a modest change in ED was observed over time. Lehmann et al 98 reported 105 cases of APL patients among whom the frequency of ED (within 30 days) actually reached 29%, a rate significantly higher than those in non-APL AML, especially evident in the elderly (460 years) population. For those EDs, 41% died from hemorrhagic complications, most of which were CNS bleeding.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Therefore, early diagnosis, and proper handling of hemorrhagic diathesis is proven to be especially important. 98 Thus, for the novo APL patients, the treatment should be further optimized. Our aim is to deliver the most timely and best treatment to each newly diagnosed APL patient, that is, to mobilize our entire human and material resources if necessary, including emergency room, intensive care unit, multi-disciplinary team of physicians and nurses, to ensure the maximum saving of lives at the onset of disease.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Despite the use of atra therapy for almost two decades, early mortality has been reduced only modestly, as recently noted in a 2011 population-based study of the Surveillance, Epidemiology, and End Results database 11 . Contrary to reported incidence rates of early death from cooperative clinical trials (which are in the 5%-10% range) 11 , recent population-based studies have shown those rates to be much higher, ranging from 17% (in a study of the Surveillance, Epidemiology, and End Results database) to 29% in a study of the Swedish Adult Acute Leukemia Registry [11][12][13] . Consistent with those findings, the results of a Canadian study by Paulson et al in 2014 showed that the incidence of early death was 22% 14 .…”
Section: Questionmentioning
confidence: 65%